2012
DOI: 10.1016/j.buildenv.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient indoor VOC air cleaning with activated carbon fiber (ACF) filters

Abstract: This study explores the potential environmental and energy benefits of using activated carbon fiber (ACF) filters for air cleaning in HVAC systems. The parallel aims for the air cleaning system were to enable reduced indoor exposures to volatile organic compounds (VOCs) and to simultaneously allow reduced rates and energy consumption for outdoor-air ventilation. We evaluated the use of ACF media to adsorb VOCs from indoor air during repeated simulated 12-hour to 24-hour periods of occupancy. In a cyclic regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(79 citation statements)
references
References 18 publications
1
76
2
Order By: Relevance
“…For the mixed VOCs, the adsorption capacity would likely be lower due to competitive adsorption of different VOC molecules (Sidheswaran et al, 2011). In contrast, the sum (250 mg) of the BTEX masses adsorbed onto 1 g of FAC obtained from the present study under the 45% RH conditions was higher than the sum of the six VOC mixture (BTX, 1-butanol, undecane, and formaldehyde) masses (90.7 mg) per gram of FAC reported by Sidheswaran et al (2012) under 30% RH. This difference is ascribed to differences in experimental parameters, such as the characteristics of FACs and the nature of the VOC mixture.…”
Section: Effect Of Rh and Ic On Adsorption Performance Of Faccontrasting
confidence: 87%
See 2 more Smart Citations
“…For the mixed VOCs, the adsorption capacity would likely be lower due to competitive adsorption of different VOC molecules (Sidheswaran et al, 2011). In contrast, the sum (250 mg) of the BTEX masses adsorbed onto 1 g of FAC obtained from the present study under the 45% RH conditions was higher than the sum of the six VOC mixture (BTX, 1-butanol, undecane, and formaldehyde) masses (90.7 mg) per gram of FAC reported by Sidheswaran et al (2012) under 30% RH. This difference is ascribed to differences in experimental parameters, such as the characteristics of FACs and the nature of the VOC mixture.…”
Section: Effect Of Rh and Ic On Adsorption Performance Of Faccontrasting
confidence: 87%
“…However, despite its widespread utilization, GAC is hampered by the highpressure drop that occurs as a result of air flow through the packed media. Fibrous activated carbon (FAC) is a recent alternative adsorbent that overcomes this drawback (Sidheswaran et al, 2012). In addition, FAC has a larger specific surface area than GAC, higher adsorption capacity, faster equilibrium for adsorption, and low pressure drop (Das et al, 2004;Fournel et al, 2005;Lorimier et al, 2005;Tsai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It respective to the energy loses and it is improved by increasing charcoal yield and make more efficient palm tree plantation in Malaysia since it very abundant ( Figure 1) [4]. According to previous researchers [5][6][7][8][9][10][11] they have produce activated carbon for air and water filter using laboratory burner and conventional burner which is not based on air flow, thermal flow calculation and not completed by fume handling system. Therefore, the conventional activated carbon is produced by high cost operation and longtime production as well as not environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, only a few studies have dealt with concentrations in the range of those found indoors. Toluene could be efficiently removed by adsorption onto activated carbon (Sidheswaran et al, 2012;Yao et al, 2012;Reguer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%